An Fe3O4@SiO2/Schiff base/Cu(ii) complex as an efficient recyclable magnetic nanocatalyst for selective mono N-arylation of primary O-alkyl thiocarbamates and primary O-alkyl carbamates with aryl halides and arylboronic acids. (17th May 2019) - Sardarian, Ali Reza; Dindarloo Inaloo, Iman; Zangiabadi, Milad
Abstract : A convenient and efficient selective mono N -arylation of primary O -alkyl thiocarbamates and carbamates is reported by a recyclable magnetic Cu(ii ) nanocatalyst. Abstract : An efficient, convenient and novel method for the selective mono N -arylation of primary O -alkyl thiocarbamates and primary O -alkyl carbamates with aryl halides and arylboronic acids in the presence of a recyclable magnetic Cu(ii ) nanocatalyst is described. A variety of mono N -arylated O -alkyl thiocarbamates and O -alkyl carbamates were prepared in good to excellent yields with a broad range of aryl coupling partners. The magnetic nanocatalyst can be easily recovered with an external magnetic field and reused at least five times without noticeable leaching or loss of its catalytic activity. This cost-effective and eco-friendly methodology has some other advantages, such as easy preparation of the catalyst, simple workup procedure, and easy purification, which makes this protocol interesting for the users in various fields of pharmacology and biotechnology systems.